Interventions addressing routine childhood immunization and its behavioral and social drivers - Shradha S. Parsekar; Lalitha Vadrevu; Monica Jain; Shekhar Menon; Gunjan Taneja (Frontiers Media S.A., 2024)
IntroductionDespite the advances in vaccination, there are still several challenges in reaching millions of children in low- and middle-income countries (LMICs). In this review, we present an extensive summary of the various strategies used for improving routine immunization in LMICs to aid program implementers in designing vaccination interventions.MethodsExperimental and quasi-experimental impact evaluations conducted in LMICs evaluating the effectiveness of interventions in improving routine immunization of children aged 0-5 years or the intermediate outcomes were included from 3ie's review of systematic reviews. Some additional impact evaluation studies published in recent years in select LMICs with large number of unvaccinated children were also included. Studies were coded to identify interventions and the barriers in the study context using the intervention framework developed in 3ie's Evidence Gap Map and the WHO's Behavioral and Social Drivers (BeSD) of vaccination framework, respectively. Qualitative analysis of the content was conducted to analyze the intervention strategies and the vaccination barriers that they addressed.Results and conclusionOne hundred and forty-two impact evaluations were included to summarize the interventions. To address attitudinal and knowledge related barriers to vaccination and to motivate caregivers, sensitization and educational programs, media campaigns, and monetary or non-monetary incentives to caregivers, that may or may not be conditional upon certain health behaviors, have been used across contexts. To improve knowledge of vaccination, its place, time, and schedule, automated voice messages and written or pictorial messages have been used as standalone or multicomponent strategies. Interventions used to improve service quality included training and education of health workers and providing monetary or non-monetary perks to them or sending reminders to them on different aspects of provision of vaccination services. Interventions like effective planning or outreach activities, follow-up of children, tracking of children that have missed vaccinations, pay-for-performance schemes and health system strengthening have also been used to improve service access and quality. Interventions aimed at mobilizing and collaborating with the community to impact social norms, attitudes, and empower communities to make health decisions have also been widely implemented.